Blumea balsamifera and Sargassum aquifolium extracts reduce fatty liver damage through lipid metabolism signalling pathways - Widhiantara, I Gede; Wiradana, Putu Angga; Permatasari, Anak Agung Ayu Putri; Sari, Ni Kadek Yunita; Rosiana, I Wayan; Sandhika, I Made Gde Sudyadnyana; Panjaitan, Novaria Sari Dewi (Universitas Nahdlatul Ulama Surabaya, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a condition marked by excessive fat accumulation in the liver and poses a significant health challenge. The leaves of Blumea balsamifera and Sargassum aquifolium have been reported to have anti-atherogenic effects. This study aims to determine the effectiveness of B. balsamifera extract (BBLE) and S. aquifolium extract (SAE) in preventing and treating liver fat accumulation in Wistar rats induced by a high-cholesterol diet through the expression of the AMP-activated protein kinase (AMPK)/ Sirtuin 1 (SIRT1)/peroxisome proliferator-activated receptor γ (PPARγ) pathway, and the leptin receptor. The experimental design of this study is laboratory-based, involving, 20 Wistar rats were fed a high-cholesterol diet over a period of 21 days. The rats were divided into four groups for the evaluation of BBLE and SAE effect: negative control (P0): induced with a high-cholesterol diet + distilled water, positive control (P1): induced with a high-cholesterol diet + simvastatin, P2: induced with a high-cholesterol diet + 4 mg/kg/bw BBLE, and P3: induced with a high-cholesterol diet + 4 mg/kg/bw BBLE and 4 mg/kg/bw SAE. The treatment duration extended over three months. Immunohistochemical analyses were performed on liver tissues to measure AMPK, SIRT1, PPARγ, and leptin receptor expression. The results indicated that leptin expression was lower in the BBLE+SAE group compared to the simvastatin group, and differences were significant between the BBLE and BBLE+SAE groups. No significant differences were noted in AMPK, SIRT1, and PPARγ expression between the simvastatin and BBLE+SAE groups (p≥0.05). In conclusion, BBLE and SAE effectively reduce liver lipid accumulation and enhance fat metabolism in hypercholesterolemic rats.